2004
DOI: 10.1021/ma035739i
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Polysulfones Containing Both Hexafluoroisopropylidene and Trimethylsilyl Groups as Gas Separation Membrane Materials

Abstract: /npsi/ctrl?action=rtdoc&an=8906267&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=8906267&lang=frAccess and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…Silylation of cellulose acetate resulted in enhanced gas permeability without significant loss of permselectivity. Especially, 1a-c displayed good performance for CO 2 separation, and their data were located either on the upper bound or above it [46,47], in the plot of permselectivity versus permeability for the CO 2 /N 2 gas pair (Fig. 5).…”
Section: Gas Separation Properties Of the Polymer Membranesmentioning
confidence: 97%
“…Silylation of cellulose acetate resulted in enhanced gas permeability without significant loss of permselectivity. Especially, 1a-c displayed good performance for CO 2 separation, and their data were located either on the upper bound or above it [46,47], in the plot of permselectivity versus permeability for the CO 2 /N 2 gas pair (Fig. 5).…”
Section: Gas Separation Properties Of the Polymer Membranesmentioning
confidence: 97%
“…It is noteworthy that membranes of 3c and 3d possessing tert-butyl groups and hydroxy groups exhibited FFV values about twice as large as those of the membranes of 3a and 3b (FFV = 0.08 and 0.10) [15]. These results suggest that the introduction of tert-butyl or trimethylsilyl groups causes the increase of the fractional free volume of the membrane, which is explicable by the idea that intersegmental packing is sterically inhibited by the presence of the bulky substituents [16].…”
Section: Solubility and Thermal Stability Of Polymersmentioning
confidence: 81%
“…mer membranes with excellent gas permeability. For example, polyacetylene derivatives as well as polysulfone [16], polyimide [17][18][19], polyphosphazene [20] and poly(ether ether ketone) [21] show higher gas permeability when tert-butyl groups and/or trimethylsilyl groups are introduced. Therefore, it is expected that poly(diphenylacetylenes) containing both tert-butyl groups or trimethylsilyl groups and hydroxy groups would show high permeability and permselectivity for CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recent studies have been directed toward designing and synthesizing of new class of processable PAs without affecting their valuable properties. Generally, an inherent trade-off between gas permeability and permselectivity exists for all the gas separation polymer membranes [7]. It is observed that the structural changes that lead to increase in permeability generally decrease the selectivity and vice versa, which was shown in Robeson upper-bound relationships [8,9].…”
Section: Introductionmentioning
confidence: 99%